Penerapan Metode Demonstrasi Uwi Kaju Kedho untuk Meningkatkan Minat Belajar Peserta Didik SMA Karitas Watuneso - Filomena Enjelina Bara; Maria Waldetrudis Lidi; Veronika P. Sinta Mbia Wae (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to assess the effect of the application of the local food-based demonstration method of Uwi Kaju Kedho on the learning interest of students at SMA Karitas Watuneso. The type of research used is quasi-experimental. The design used in this study is a nonequivalent control group. The bound variable in this study is the students' learning interest, while the free variable is the demonstration method based on local food uwi kaju kedho. The population in this study is 123 students in class X, and the research sample is 48 people obtained by purposive sampling technique. The data obtained from the research sample was in the form of a questionnaire. Data analysis was carried out by t-test using the help of SPSS 25 for windows. The results of the study show that the application of local food-based demonstration methods has an effect on the learning interest of students at Karitas Watuneso High School. This can be seen from the results of the study interest questionnaire and observation. The average questionnaire score was 76.10 and the average observation score was 100. The results of the t-test supported the difference in learning interest between the control and experimental groups.